Geochemical Characterization of Insoluble Particle Clusters in Ice Cores Using Two‐dimensional Impurity Imaging - Bohleber, Pascal; Stoll, Nicolas; Rittner, Martin; Roman, Marco; Weikusat, Ilka; Barbante, Carlo (Geochemistry, Geophysics, Geosystems, 2022)
Understanding post-depositional processes altering the layer sequence in ice cores is especially needed to avoid misinterpretation of the oldest and most highly thinned layers. The record of soluble and insoluble impurities represents an important part of the paleoclimate proxies in ice cores but is known to be affected through interaction with the ice matrix, diffusion and chemical reactions. Laser ablation inductively-coupled plasma mass spectrometry (LA-ICP-MS) has been recognized for its micron-scale resolution and micro-destructiveness in ice core impurity analysis. Employing LA-ICP-MS for 2D chemical imaging has already revealed a close relationship between the ice grain boundary network and impurity signals with a significant soluble component, such as Na and Mg. Here we show the latest improvements in chemical imaging with LA-ICP-MS, by increasing the spatial resolution to 20 μm and extending the simultaneous analysis to also mostly insoluble impurities, such as Al and Fe. All analytes reveal signals of dispersed spots in a sample of an East Greenland ice core. Based on their average size around 50-60 times larger than an average particle and their heterogeneous elemental ratios these spots are interpreted as particle clusters. To distinguish their origin, a simple colocalization classification reveals elemental ratios consistent with marine and mineral dust aerosol. Based on already existing data from cryo-Raman spectroscopy, we discuss potential ways to integrate the two methods in a future comparison. Such a combined approach may help constraining post-depositional changes to the dust-related insoluble impurity components, such as cluster formation and chemical reactions at grain boundaries.